Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1086/524882
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Nuclear Anomalies in Planetesimal Cores

Abstract: Use of the extinct 182 Hf-182 W chronometer to constrain the timing of planetary accretion and differentiation rests on the assumption that the solar nebula had homogeneous tungsten isotopic composition. Here, we report deficiencies of $0.1 part in 10,000 in the abundance of 184 W in group IVB iron meteorites relative to the silicate Earth. These are most likely due to incomplete mixing at the planetesimal scale (2Y4 km radius bodies) of the products of slow (s-) and rapid (r-) neutron-capture nucleosynthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
72
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 43 publications
11
72
3
Order By: Relevance
“…However, the s-process path in the Hf-Ta-W-Re-Os region of the nuclide chart is not well understood (e.g., Ávila et al 2012), making such predictions uncertain. In contrast, the new W isotopic data presented here provide the first direct measurement of correlated nucleosynthetic effects on the different W isotopes, and as such provide a powerful means for quantifying nucleosynthetic anomalies on ε 182 W. Qin et al (2008b), using Maxwellian-averaged cross sections (MACS) from Bao et al (2000) Qin et al (2008b) also noted that the MACS of Bao et al (2000) led to a predicted r-process 182 W residual abundance that was too high, and suggested that this overproduction problem may be resolved if the MACS value of 182 W was reduced by ≈20%. Using the modified value, a slope of ≈0.5 was obtained for the ε 182 W-ε 184 W correlation line.…”
Section: Nucleosynthetic W Isotope Anomalies In Cai and The Initial Wmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the s-process path in the Hf-Ta-W-Re-Os region of the nuclide chart is not well understood (e.g., Ávila et al 2012), making such predictions uncertain. In contrast, the new W isotopic data presented here provide the first direct measurement of correlated nucleosynthetic effects on the different W isotopes, and as such provide a powerful means for quantifying nucleosynthetic anomalies on ε 182 W. Qin et al (2008b), using Maxwellian-averaged cross sections (MACS) from Bao et al (2000) Qin et al (2008b) also noted that the MACS of Bao et al (2000) led to a predicted r-process 182 W residual abundance that was too high, and suggested that this overproduction problem may be resolved if the MACS value of 182 W was reduced by ≈20%. Using the modified value, a slope of ≈0.5 was obtained for the ε 182 W-ε 184 W correlation line.…”
Section: Nucleosynthetic W Isotope Anomalies In Cai and The Initial Wmentioning
confidence: 92%
“…A heterogeneous distribution of these different phases would produce nucleosynthetic W isotopic anomalies, which may affect the use of the 182 Hf-182 W system to infer the timescales of early solar system processes. However, with the exception of small 184 W deficits in IVB iron meteorites (Qin et al 2008b) Qin et al 2008b). However, the s-process path in the Hf-Ta-W-Re-Os region of the nuclide chart is not well understood (e.g., Ávila et al 2012), making such predictions uncertain.…”
Section: Nucleosynthetic W Isotope Anomalies In Cai and The Initial Wmentioning
confidence: 99%
“…The parent body of angrites is 4564.42 ± 0.12 Ma old (Amelin 2008) and Quitté et al (2010) determined that its initial 60 Fe/ 56 Fe ratio is ≈(3.1 ± 0.8) × 10 −9 . Although tungsten isotope evidence (Schersten et al 2006;Qin et al 2008) indicates that most iron meteorites are formed within a few Ma of CAIs, they show no evidence of having 60 Ni excesses (Markowski et al 2006). The exact ages of these samples, however, remain poorly determined.…”
Section: Introductionmentioning
confidence: 99%
“…After the Arlandini et al (1999) paper was published, the neutron capture cross section of 182 Ta was revised downward by 50%, which increased the production of 182 W by 40%. This has been discussed in (Qin et al, 2008). We discuss the issue further below (Fig.…”
Section: Nucleosynthesis Effectsmentioning
confidence: 87%
“…However, a series of recent studies using high precision multiple collector-inductively-coupled-plasma-mass spectrometry (MC-ICP-MS) and thermal ionization mass spectrometry (TIMS) have revealed that the isotopic homogeneity for many elements in meteoritic materials are not warranted (e.g., Mo, Yin et al, 2002b;Dauphas et al, 2002;Becker and Walker, 2003;Ba, Hidaka et al, 2003;Ranen and Jacobsen, 2006;Carlson et al, 2007;Nd, Sm, Andreasen and Sharma, 2006;Carlson et al, 2007;Cr, Trinquier et al, 2007;Ni, Regelous et al, 2008;W, Qin et al, 2008;Os, Brandon et al, 2005;Yokoyama et al, 2007). Qin et al (2008) first reported the significant level of 184 W deficiencies iñ 0.1ε units from the IVB iron meteorites. The resulting variations in the isotopic composition of 184 W found in the IVB iron meteorites was attributed to reflect the heterogeneous distribution of s-and r-process nuclides at the nebula scale for the source materials of parent body of the IVB irons accreted (an asteroid of ~2-4 km radius; Haack et al, 1990).…”
Section: Introductionmentioning
confidence: 99%